Ensinando a ensinar ou vivendo para aprender? A interação entre os conhecimentos de um professor atuante e de um aspirante, como subsídio para aprendizagem da docência. - Longhini, Marcos Daniel (2006)
Contrary to what is known as process-product researches, in which teachers used to be seen as a mere technical performer, nowadays the teacher is the centerpiece in the educational process. In this new approach, the teacher is the core of the debates and professional practices, personal life and know-how of the professional practices are analysed. Lee Shulman is one of the researchers who tries to make a list of required knowledge for a teacher to carry out his/her job. This list is referred to as knowledge base of teaching by the author, which is formed, mainly, by content knowledge, general pedagogical knowledge and pedagogical content knowledge. As one of the sources to acquire such knowledge is the everyday practice, we have asked in which aspects and how a veteran teacher and a teacher-to-be, working together in their development process, and having a training teacher as mediator, can share the required knowledge in teaching. Two professionals graduated in Education and the researcher, in the role of mediator, took part in this study. One of the professionals, referred to as teacher-to-be, had no classroom practice; the other, referred to as veteran teacher, had an eighteen-year-long experience. Data was gathered from August through December 2003. The focal point was the elaboration, implementation and reflection about a series of five classes taught to early grades in Elementary School, the subject being air . The focus was the knowledge that is part of the knowledge base of teaching pointed out by Shulman. Results showed that the teacher-to-be faced the same difficulties and experienced similar tensions and anxiety as her veteran peer when at the beginning of her career. However, after years of practice, the veteran teacher seemed to have solid techniques or strategies on how to deal with students, differently from the teacher-to-be, who still tried to build them up by a process of trial and error. The greatest interaction between them was about the general pedagogical knowledge , when they talked about strategies to control students discipline, their characteristics and their behavior during classes. Both presented an important lack of content knowledge , which made it difficult for them to understand each other when that was the point. They had different motivation concerning the focus of analyses of the classes and about what they wanted to learn: the teacher-to-be focused on her own performance while the veteran teacher looked at the learning process by the students. Such fact might show that, instead of helping the development process, the longer the practice the more difficult for the peers to interact since the teachers interests could be different. Accepting an opinion or idea from a peer seems to be tied more to private characteristics of those involved. Contrary to what was expected, i.e., that the teacher-to-be could learn more about how to teach from the veteran teacher, there was learning by both professionals and an improvement in their knowledge base of teaching .